Wave propagation along an edge of a solid - Wincenty PAJEWSKI; Marek SZALEWSKI; Paweł KIEŁCZYŃSKI (Archives of Acoustics)
Investigation results of waves propagating along edges of isotropic and anisotropic bodies are presented in this paper. Also methods of producing wave-guides, generation methods of line waves, the influence of anisotropy on distribution of vibrations and applications of these waves in the acoustic convolution process are discussed.